Growth, Research & Development, and Uncertainty: An Empirical Analysis in Finland - Walters, Stephen (Asian Journal of Economics and Empirical Research, 2020)
Invention and innovation are the most important aspects in the growth and development of a country. Investors come up with innovative ideas that can play a role in the development of technology in the country. The research and development (R&D) sector is very much associated with this, as it comprises researchers who have the ability to think creatively and come up with innovative ideas and designs for firms. It can be stated that countries where the research sector is well-developed and well-maintained have a greater chance to enjoy better economic growth (EG). The core purpose of the current study is to understand the influence of R&D and uncertainties associated with R&D on the EG of Finland. Based on this context, the researcher has gathered data on relative variables in Finland for 29 years and applied a stochastic model. The results obtained show that uncertainty in the research sector has a negative influence on the EG in Finland. The results also indicate the fact that, as uncertainty in the research sector increases, the distribution or allocation of human capital will shift from the research sector to the final goods sector. Moreover, it was also found that uncertainty has a negative impact on welfare. This study has significant implications for the R&D sector in Finland, in the sense that it has the potential to guide the research sector towards improvement through an increase in the number of patents and the establishment of research institutions that can reduce impact of uncertainty.